Editorial: Knowledge graph technologies: the next frontier of the food, agriculture, and water domains - Roussey, Catherine; Guéret, Christophe; Laporte, Marie-Angelique (Frontiers Media, 2023)
EDITORIAL article Front. Artif. Intell., 28 November 2023Sec. AI in Food, Agriculture and Water Volume 6 - 2023 | https://doi.org/10.3389/frai.2023.1319844